Verses That Crilicize and Praise the Poets In Surat (Al-Shuara) –An Analytical Study- (Islamic Sciences Journal, 2023)
The verses of the Noble Qur’an are the secret of the beauty of Arabic, and its striking charm, where we notice the beauty of his portrayal and the beauty of his expression of huge issues and connotations in a space in which it is impossible for humans to express such purposes in the broadest and most accurate expression with the strange harmony between a statement and its meaning, as is the case of  the verses where The poets were criticized and praised, We stood on the secret of miracles in the diversity of the Qur’anic vocabulary that had a prominent role in depicting the Qur’anic meaning, and the linguistic and semantic secrets it contained, as well as the structures that were built from them and the methods in which they were used to clarify their purposes and the purpose for which they were directed, and that is in two sections, The first group deals with the discussion of Qur’anic vocabulary in two groups: the first one talked about the names that are mentioned in them, and the second one: the actual formulas in which they are used. As for the second section: the types of the Qur’anic sentence are separated into two groups, the first: in the defamation of poets, and the second in praising of the poets. Then a conclusion that summarized what have been mentioned.